P6.071 Projects for Strengthen Civil Society's Actions Related to the STD/HIV/AIDS and Viral Hepatitis Epidemic. (13th July 2013) - Correia, N; Lima, N; Seara, L; Colombo, M; Oliveira, D; Casimiro, G; Barbosa, B
Abstract : Background: Since 1999, the Brazilian STD, AIDS and Viral Hepatitis Program has funded Civil Society projects selected through public calls for proposals for strengthening health promotion campaigns. The priority populations are people living with HIV/AIDS (PLWHA), carriers of viral hepatitis, and segments of the population at greater risk of contracting STDs. Methods: Strengthening of campaigns and field interventions for populations in circumstances of great vulnerability to STDs, HIV/AIDS and viral hepatitis, taking into consideration the epidemiological relevance of each region; Expansion of systemic educational interventions that contribute to broaden and improve diagnosis, prevention, health promotion, and human rights relative to STDs, HIV/AIDS and viral hepatitis; Campaigns to reduce the harm caused by alcohol and drugs, with a focus on prevention, health promotion, and STD, HIV/AIDS and viral hepatitis diagnosis; Participation by PLWHA and/or carriers of viral hepatitis in the formulation of policies, thus contributing to the improvement of the organisation of services, community mobilisation, and societal control; Actions to reduce stigma and discrimination related to living with HIV/AIDS and viral hepatitis, and promotion of the usage of prevention inputs. Results: From 1999 to 2012, 6, 419 projects were financed, totaling R248, 764, 148.54 (approximately U 124 million). The results of the projects contribute to health promotion campaigns by strengthening and/or expanding actions for: the prevention of STD/HIV/AIDS, encouraging STD/HIV/AIDS diagnosis, prevention, societal control, legislation, and implementation of integrated strategies in public services. Conclusion: Governmental budget is an important key to strength and support the civil society organisations in their participation on development and implementation of healthcare promotion policies.